An experimental and numerical study of forming limits of AA5182-O. Issue 1 (July 2015) - Ju, Long; Mao, Tingting; Li, Hongbo
Abstract Forming limit curve (FLC) has been applied for evaluating the formability of sheet metal in a standardized way. Various experimental procedures and theoretical models were introduced in the past decades. However, bunches of tests required in the experimental determination of FLC make the procedures more burdensome. In the present study, a combination of experiment and simulation study was conducted with AA5182-O in terms of localized necking and fracture. In the proposed methodology, three experimental procedures, uniaxial tensile, deep drawing with round cup, and dome stretching, were performed and analyzed by using the finite element (FE) simulations. The feasibility of FE models were preliminarily examined by the experimental results. The progression-dependent criterion was developed to determine the process of localized necking to fracture. In the criterion, evolutions of principal strains and their derivatives were calculated and calibrated by validated FE models. The limiting strains obtained from the proposed method showed a good agreement with FLCs obtained using other methods.